Report on proposed new interior design of Restoran Sari Ratu authentic Nasi Padang for Sari Ratu Prima Sdn Bhd at No. 16 & 18, Jalan 4/76C, Desa Pandan, 55100 Kuala Lumpur / Nurul Nadzira Mohd Farid - Mohd Farid, Nurul Nadzira (Faculty of Architecture, Planning and Surveying, 2010)
Diploma in Interior Architecture final project is a manifestation of the student towards the understanding of all aspects of interior architecture process that has been learned from the most basic stage to the presentation of the proposed design stage The chosen project for subject INA316 is proposing a new interior for an authentic Nasi Padang restaurant that is Restoran Sari Ratu in Desa Pandan, Kuala Lumpur. The purpose of this project was to introduce the Minang food in a greater depth to the public, especially towards the local people. Thus, with the launching of this particular restaurant branch, local people are able to enjoy the healthy food of Minang and are exposed to the Minang culture. On carrying out this project, the interest is clearly visible to the promotion of eating cooked food directly to the public. This will reduce the habit of some people who like to choose fast food over cooked food as their daily menu which is known as less healthy. The method of study used in this project is based on the observations of local and foreign restaurants. In conclusion, the new design should be carried out correspondently to the characteristics and needs of customers in line with the concepts to be highlighted. Last but not least, the design is expected to provide benefits to all individuals, whether foreigners or local people in this country.